Implementation of the Cooperative Learning Model Type (STAD) in Improving Student Learning Outcomes in PAIBP Subjects in Class XI TITL 1 SMKN 1 Purwakarta - Hanna Kamilah; Asti Nurul Islami; Rhamdani Putra Pratama; Puja Kharunnisa; Rhana Cahya Nugraha; Muhammad Syabani Ridwanulloh (Journal of Innovative and Creativity, 2025)
This study aims to improve student learning outcomes in Islamic Religious Education and Ethics (PAIBP) in class XI TITL 1 at SMKN 1 Purwakarta through the application of the Student Team Achievement Division (STAD) cooperative learning model. This study used the Classroom Action Research (CAR) method, which was carried out in two cycles. The research subjects consisted of 36 students. Each cycle consisted of the planning, implementation, observation, and reflection stages. The STAD model was applied through five main components: class presentations, teamwork, individual quizzes, progress scores, and team awards. In cycle I, the average student score was 69 with a classical mastery level of 50%. After improvements were made in cycle II, the average score increased to 81 and the classical mastery level reached 92%. Student learning activities also increased significantly, marked by active participation in group discussions and increased learning motivation. The STAD cooperative learning model is effective in improving student learning outcomes and motivation. This approach encourages cooperation, critical thinking, and a passion for knowledge in accordance with Islamic values